A-68 Neuropsychological Predictors of Seizure Freedom in Patients Undergoing Stereotactic Laser Ablation of the Hippocampus (SLAH) for Refractory Epilepsy. (30th August 2021) - Park, Sydney E; Cummings, Tiffany L; Rigdon, Joseph; Robles, Christian; Bhaskar, Brinda; Horn, Alex; Allen, Calisha; Flashman, Laura; Peterson, Keyan; Lemley, Regan; Liberatore, Grace; Morgan, Katie; et al.
Abstract: Objective: Presurgical cognitive and psychiatric status can serve as predictors of surgical outcomes; however, there are no studies that assess the predictive nature of cognitive factors and psychiatric illness on seizure freedom following stereotactic laser ablation, a novel, minimally invasive surgical approach, of the hippocampus (SLAH). Therefore, this study aimed to assess whether neuropsychological factors were associated with long-term postoperative outcome, defined as time maintaining continuous postoperative seizure freedom (Engel Class I outcome persistently after surgery), after mesial temporal laser ablation surgery. Method: Forty-one patients (Age M = 37.5 ± 12.6; 61% female; 63% left mesial temporal ablation; 37% right mesial temporal ablation) were selected from retrospective data collection of epilepsy surgery outcomes following mesial temporal laser ablation. Patients were assessed with a presurgical neuropsychological battery as part of Phase I work-up. Results: Wilcoxon rank-sum tests revealed there were no significant differences between groups (seizure free and non-seizure free) across presurgical intellectual functioning, (seizure free M = 37.6; non-seizure free M = 40.6; p = 0.31), verbal memory (p = 0.59), visual memory (p = 0.39), and language composite scores (p = 0.87). There was also no significant difference in presurgical mean depression scores (p = 0.81). Conclusions: There were no significant differences between groups in presurgical cognitive and psychiatric predictors on seizure outcomes; however, sample size is a limitation. Further investigations are needed given that cognitive and psychiatric predictors may be associated with SLAH outcomes. Additionally, these findings add to the absence of literature on cognitive and psychiatric predictors in SLAH.